Churchill and Spain : the survival of the Franco regime, 1940-45 - Wigg, Richard, 1928- (Routledge/Cañada Blanch studies on contemporary Spain., 2005)
This thoroughly researched, highly perceptive and utterly gripping study deals with an important aspect of Spanish and British history - Churchill's policy of appeasement toward the Franco regime in Spain. Wigg demonstrates that the tolerance shown toward Spain's wartime trading permitted the rebuilding of Spanish gold reserves which helped Franco survive his (and Spain's) international ostracism between 1945 and 1950. This important book will interest scholars with an interest in contemporary European political history as well as those with a general interest in Spanish histor.